B→πℓ+ℓ− form factors reexamined in the whole kinematically accessible region - Zuo-Hong Li; Zong-Guo Si; Ying Wang; Nan Zhu (Nuclear Physics B, 2015)
We reexamine the B→πℓ+ℓ−(ℓ=e,μ,τ) form factors, f+B→π(q2), f0B→π(q2) and fTB→π(q2), in the entire region of the momentum transfer squared q2, by taking advantage of the complementarity between lattice QCD (LQCD) simulation and light cone sum rule approach (LCSR), and analyticity of the form factors. A LCSR calculation with a chiral current correlator, which could avoid pollution by twist-3 components, is performed at twist-2 next-to-leading order (NLO) accuracy, to determinate the form factor shapes in the small and intermediate q2 region. Further, fitting simultaneously the LCSR results for these form factors and the related LQCD ones (available or based on a SUF(3) symmetry breaking ansatz) to a Bourrely–Caprini–Lellouch (BCL) parametrization, we get a global understanding of their q2 behaviors. Our findings turn out to be consistent with the recent study by Ali, Parkhomenko and Rusov, and the resulting observation for the vector form factor provides support for the existing LQCD as well as LCSR predictions extrapolated to the entire kinematically accessible region.